Pilot Clinical Trial of Indocyanine Green Fluorescence-Augmented Colonoscopy in High Risk Patients. (17th February 2016) - Sheth, Rahul A.; Heidari, Pedram; Woods, Kevin; Chung, Daniel; Chan, Andrew T.; Mahmood, Umar
Abstract : White light colonoscopy is the current gold standard for early detection and treatment of colorectal cancer, but emerging data suggest that this approach is inherently limited. Even the most experienced colonoscopists, under optimal conditions, miss at least 15–25% of adenomas. There is an unmet clinical need for an adjunctive modality to white light colonoscopy with improved lesion detection and characterization. Optical molecular imaging with exogenously administered organic fluorochromes is a burgeoning imaging modality poised to advance the capabilities of colonoscopy. In this proof-of-principle clinical trial, we investigated the ability of a custom-designed fluorescent colonoscope and indocyanine green, a clinically approved fluorescent blood pool imaging agent, to visualize polyps in high risk patients with polyposis syndromes or known distal colonic masses. We demonstrate (1) the successful performance of real-time, wide-field fluorescence endoscopy using off-the-shelf equipment, (2) the ability of this system to identify polyps as small as 1 mm, and (3) the potential for fluorescence imaging signal intensity to differentiate between neoplastic and benign polyps.